Works on paper. - Vuorikoski, Timo; Exhibition. Works on paper. Sara Hilden Art Museum Tampere. 2003 (Tampere : Sara Hilden Art Museum Tampere, 2003)
Bellmer, Hans ; Bissier, Julius ; Blais, Jean-Charles ; Bonnard, Pierre ; Buraglio, Pierre ; Christo ; Cucchi, Enzo ; Delvaux, Paul ; Fautrier, Jean ; Ipousteguy, Jean ; Klee, Paul ; Kolar, Jiri ; López, Francisco ; Merz, Mario ; Miro, Joan ; Molin, Lei ; Motherwell, Robert ; Peinado, Francisco ; Picasso, Pablo ; Quintanilla, Isabel ; Quintero, Daniel ; Rouault, Georges ; Schwitters, Kurt ; Scott, William ; Solano, Susana ; Tanguy, Yves ; Titus-Carmel, Gérard ; Tobey, Mark ; Vasarely, Victor ; Velickovic, Vladimir ; Venet, Bernar ; Vieira da Silva, Maria Elena ; Wols
biog., tent., bibliog. per kunstenaar [1 p.]
Engels
Fins
boek